Academic preparedness of Pamantasan ng Lungsod ng Maynila College of Nursing Batch 2012 for the nurse licensure examination: A basis for developing an enhancement program - Alhambra, Abigail G.; Ancheta, Charmaigne Dune S.; Balahula, Jermela D.; Bisleg, Mae Angeli N.; Bool, Karmela P.; Catacutan, Katrina Marie V, and Clemente, Ace Virgil F. 4 0 16; 5 (2011)
u
Undergraduate (Thesis) Pamantasan ng Lungsod ng Maynila.;College of Nursing, Bachelor of Science in Nursing.
Keywords: 2 -- 0; 6; 20; 20; 2